2018
DOI: 10.1007/s10815-018-1202-9
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent complete hydatidiform mole: where we are, is there a safe gestational horizon? Opinion and mini-review

Abstract: Benign hydatidiform mole, complete or partial, is the most common type of gestational trophoblastic disease (GTD) characterised by excessive trophoblastic proliferation and abnormal embryonic development. Although most complete hydatidiform moles (CHMs) are diploid androgenetic, a few cases of CHMs are biparental, characterised by recurrence and familial clustering. In these rare cases, mutations in NLRP7 or KHDC3L genes, associated with maternal imprinting defects, have been implicated. Current data regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…This suggests that it may coordinate cytokines secretion and transportation (Messaed et al 2011). In addition, NLRP7 is referred to as a maternal-effect gene, whose mutations commonly result in recurrent hydatidiform moles (RHMs), a gestational trophoblastic disease characterized by a mass exhibiting trophoblastic hyperplasia and swelling of chorionic villi as well as impaired embryonic development (Murdoch et al 2006, Sebire et al 2013, Nguyen et al 2014, Carey et al 2015, Ito et al 2016, Sills et al 2017, Kalogiannidis et al 2018). The homozygous or compound heterozygous NLRP7 missense and non-sense mutations in male do not jeopardize their normal reproductive outcomes and this indicates that NLRP7 may specifically regulate female reproduction (Qian et al 2007, Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that it may coordinate cytokines secretion and transportation (Messaed et al 2011). In addition, NLRP7 is referred to as a maternal-effect gene, whose mutations commonly result in recurrent hydatidiform moles (RHMs), a gestational trophoblastic disease characterized by a mass exhibiting trophoblastic hyperplasia and swelling of chorionic villi as well as impaired embryonic development (Murdoch et al 2006, Sebire et al 2013, Nguyen et al 2014, Carey et al 2015, Ito et al 2016, Sills et al 2017, Kalogiannidis et al 2018). The homozygous or compound heterozygous NLRP7 missense and non-sense mutations in male do not jeopardize their normal reproductive outcomes and this indicates that NLRP7 may specifically regulate female reproduction (Qian et al 2007, Wang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to POC results of another group [12], the prevalence of wgUPD in our study was similar (0.47% vs. 0.5%), but the prevalence of triploidy in our study was lower (3.9% vs. 6.3%). Aside from the rare recurrent CHM with a biparental diploid karyotype, which is an autosomal recessive disease called familial recurrent HM (FRHM) due to biallelic mutations in 2 genes: NLRP7 at 19q13.42 [15] [16], and more rarely, KHDC3L at 6q13 [17], the genetic abnormalities associated with cases of triploidy with PHM, and the wgUPD associated with CHM can be reliably detected by oligo-SNP based CMA; correlation with clinical findings, histopathological features, p57 (KIP2) immunohistochemistry, and genotyping results may ensure accurate classification in equivocal cases [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, a pioneer study reported for the first time that biallelic KHDC3L mutations caused the familial complete hydatidiform mole [31], an extreme infertility condition that is characterized by early embryonic arrest and excessive trophoblastic proliferation. The observed phenotype was attributed to abnormal maternal gene imprinting [71,72]. Follow-up studies also identified several other biallelic mutations of KHDC3L that are causal to complete hydatidiform mole [68,73].…”
Section: Discussionmentioning
confidence: 99%